Aerobic fitness and muscle density play a vital role in postoperative complications in colorectal cancer surgery. Issue 6 (11th February 2022) - Cuijpers, Anne C. M.; Bongers, Bart C.; Heldens, Aniek F. J. M.; Bours, Martijn J. L.; van Meeteren, Nico L. U.; Stassen, Laurents P. S.; Lubbers, Tim
Abstract: Background and Objectives: To assess the association of preoperative aerobic fitness and body composition variables with a patient's resilience to the development and impact of postoperative complications after elective colorectal cancer (CRC) surgery. Methods: Preoperative aerobic fitness was assessed by steep ramp test performance. Preoperative body composition was assessed by muscle mass and density determined from preoperative computed tomography scan analysis at the L3‐level. Complication development and severity was graded according to Clavien‐Dindo. Complication impact was assessed by the time to recovery of physical functioning after complications. Multivariable logistic regression analyses adjusted for age, sex, comorbidities and tumour location was performed. Results: Of 238 included patients, 96 (40.3%) developed postoperative complications. Better preoperative aerobic fitness decreased the likelihood to develop complications, independent of muscle mass (odds ratio [OR]: 0.55, 95% confidence interval [CI]: 0.35−0.85) or muscle density (OR: 0.57, 95% CI: 0.36−0.89). A prolonged time to recovery following complications was associated with lower preoperative muscle density (OR: 4.14, 95% CI: 1.28−13.41), independent of aerobic fitness. Conclusions: Lower aerobic fitness increases the risk of complication development, while low muscle density seems associated with a prolonged recovery from complications. Aerobic fitness and muscle density could be valuable additives to preoperative risk assessment.